Clarification of a unique mucosal vaccination route for improved systemic and mucosal immune response in broiler - Rupa Akter; Md Abdul Masum; Subrato Biswas; Md Zahir Uddin Rubel; Sujan Kumar Sarkar; Mohammad Saiful Islam; Hossain M. Golbar; Md Emtiaj Alam; Md Abdur Rakib; Md Zahirul Isalm Khan (Heliyon)
There are often outbreaks of infectious diseases on farms, which not only disrupt production but also cause significant economic losses. Vaccines are given to prevent the spread of these infectious diseases, but they produce only systemic antibodies or antibodies in the mucosa of a particular system. So, a new mucosal vaccination route is needed where the vaccine will produce antibodies in the systemic circulation as well as in the mucosa of many systems. In our study, the cloaca was targeted because it is associated with the mucosa of many systems. Whole-mount and routine histological staining show both lymphatic nodules and diffuse lymphatic tissues in the lamina propria of cloaca. These lymphatic tissues are made up of Bu-1+ B-cells, CD3+ T-cells, and KUL01+ macrophages and monocytes. So, this is a new mucosa-associated lymphoid tissue, named cloaca-associated lymphoid tissue (CALT). The CALT contains antigen-presenting cells (dendritic cells, macrophages, B cells, MHC II molecules, and T cells) and is equipped with blood vessels and high endothelial venules, which indicate its functional status. More antibodies were produced in the treatment group compared to the vehicle control group after administration of the infectious bursal disease (IBD) and the Newcastle disease (ND) vaccine through cloaca. In addition, the cloaca-associated route produces a higher number of antibodies than the other traditional routes, which reveals the uniqueness of this route. Cloacal-vaccinated chickens showed less damage to the follicle and epithelium of the bursa of Fabricius compared to other groups, indicating its lower cytotoxic effect. Therefore, the cloaca-associated mucosal vaccination route produces more antibodies than other mucosal vaccination routes, which will protect the chickens on the farm to a greater extent.